2012
DOI: 10.2500/ajra.2012.26.3705
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Surgical and Comprehensive Postoperative Medical Management for Cystic Fibrosis Chronic Rhinosinusitis

Abstract: Background: Chronic rhinosinusitis has a major impact on the quality of life of patients with cystic fibrosis (CF)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
136
1
5

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(146 citation statements)
references
References 34 publications
4
136
1
5
Order By: Relevance
“…The delivery volume of 60 mL is also inadequate according to data from Buele's study, which proposed using a volume of 100 mL for an effective irrigation. 66 Data were not available for meta-analysis because there was no placebo group as per the other included RCTs. In contrast to the Rotenberg study, Lavigne and colleagues 39 reported positive outcomes when 256 g of budesonide was administered through a maxillary sinus catheter in postoperative CRS patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The delivery volume of 60 mL is also inadequate according to data from Buele's study, which proposed using a volume of 100 mL for an effective irrigation. 66 Data were not available for meta-analysis because there was no placebo group as per the other included RCTs. In contrast to the Rotenberg study, Lavigne and colleagues 39 reported positive outcomes when 256 g of budesonide was administered through a maxillary sinus catheter in postoperative CRS patients.…”
Section: Discussionmentioning
confidence: 99%
“…There is also variability between different delivery methods in the studies analyzed. Effective sinus distribution requires multiple factors 13 such as positive pressure, large volumes, 66 and various sinus ostial dimensions after ESS. 9 Greatest distribution is likely to be achieved when a wide post-ESS corridor has been created regardless of delivery method.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent prospective study, FESS and MEMM combined with a comprehensive postoperative medical management regimen (culture-directed antibiotics, oral steroid taper, and topical steroid/ antibiotic irrigations) was associated with marked improvement in sinus disease outcomes including a decrease in symptoms (22-item Sino-Nasal Outcome Test) and objective findings (Lund Kennedy scores) at 1 year of clinical follow-up. 145 In this study, FEV 1 was not significantly changed, but there was significant reduction in the hospital admissions for pulmonary exacerbations in the year postsurgery compared with the year before. Results from these investigations lends support to a more extensive surgical approach in CF sinusitis, but further studies are warranted to determine whether this treatment paradigm will provide longterm symptom improvement and confer advantages in CF pulmonary outcomes.…”
Section: Novel Therapeutics: Targeting the Basic Defectmentioning
confidence: 76%
“…Intranasal glucocorticoids have been demonstrated to decrease nasal obstruction and nasal polyp size in CF patients [19]. Nasally nebulized dornase alfa, culture directed oral or systemic antibiotics, and topical antibiotic irrigation have all demonstrated benefit in CF patients after sinus surgery [20][21][22]. Less data is available for PCD, but current guidelines for general treatment of include daily chest physiotherapy and cardiovascular exercise as routine therapy, with antibiotics reserved for acute exacerbations [6,23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of cystic fibrosis (CF), another recessive genetic disease with impaired mucociliary clearance, has been more substantially studied [18][19][20][21][22]. Intranasal glucocorticoids have been demonstrated to decrease nasal obstruction and nasal polyp size in CF patients [19].…”
Section: Discussionmentioning
confidence: 99%